Consumers’ Attitudes Towards Whole Dried Figs Attributes: A Preliminary Study in Italy - Federica Monaco; Pietro De Marinis; Guido Sali (Agriculture)
Dried fig production and trade are prominent in Mediterranean and Middle east countries, with Turkey as the major player. Concerns about the quality of Turkish supply in the EU market give chances to the Italian production to uphold quality standards and cope with the increasing demand. National consumption of dried figs is showcased in market reports and nutritional surveys, with insufficient insights on consumers’ preferences. This research combines qualitative and quantitative approaches to enrich the current knowledge and uncover consumers’ attitudes towards whole dried figs. A face-to-face survey was conducted to assess the relevance of selected intrinsic, extrinsic and credence attributes upon purchasing. A hierarchical cluster analysis detected four typologies of consumers and validate previous findings on taste being the prime purchasing driver. Price affects more the behaviour of low-income large families; the groups are featured by contrasting opinions on environmental and societal impacts of dried fig production, and its rootedness to the local context. This allowed to draft some considerations on possible marketing strategies tailored to different consumers.